PENGARUH CAMPURAN AMPAS TEH DAN AMPAS TEBU TERHADAP PERTUMBUHAN CABAI MERAH KERITING (Capsicum annum L.) - Alfin Oktajaya Telaumbanua; Hulu, Versi Putra Jaya (Universitas Nias Raya, 2023)
Based on the background of the research problem, there is a lack of understanding, especially by the Desa Sukamaju Mohili community, in utilizing a mixture of tea dregs and bagasse in curly red chili plants, where the community still uses inorganic (chemical) fertilizers thereby degrading soil quality. This study aims to determine the effect of a mixture of tea dregs and bagasse on the growth of curly red chili (capsicum Anmum L). This type of research is quantitative with a pure experimental method (true experiment) with a completely randomized design (CRD). The population of this study was curly red chili as much as 20 polybags and the research sample was curly red chili with five treatments and four replications. The treatments applied were P0 (without adding a mixture of tea bagasse and bagasse) P1 (100 grams), P2 (200 grams), P3 (300 grams), and P4 (400 grams). The research data were analyzed using the Kolmogrov-Smirnov test for normality test, homogeneity test and hypothesis testing using the SPSS application (produc and service solution statistics) version 22. The asymp embodiment of 0.035 <0.05 indicates that the stem height of curly red chilies is better than those without using a mixture of tea bagasse and bagasse while it is known that the asymp value is 0.048 <0.05 indicating that the number of leaves of curly red chili plants is greater than those who do not use a mixture of tea bagasse and bagasse. The suggestions offered by researchers, for farmers are expected to be information that bagasse and tea bagasse can have an effect on the growth of curly chilies for students of teaching and education faculties, especially biology education, I hope this research can add insight and knowledge about the effect of bagasse and tea bagasse as on the growth of curly red chili (capsium Anmum L), for future researchers, as a basis for the development of further research on the effect of bagasse and dregs as a plant medium on the growth of curly red chili (capsium annmum L).